LEGAL POLICY ON COPYRIGHT OF DIGITAL WORKS BASED ON ARTIFICIAL INTELLIGENCE IN THE CREATIVE ECONOMY ERA IN INDONESIA - Rara Amalia Cendhayanie; Megawati Barthos (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
The swift evolution of Artificial Intelligence (AI) has facilitated the production of digital creations via computational algorithms, prompting juridical questions about authorship, novelty, and safeguards under copyright law. In Indonesia, the copyright system—chiefly regulated by Law No. 28 of 2014—upholds humans exclusively as eligible creators. This stance engenders difficulties in providing juridical predictability for outputs produced by or with AI assistance, especially amid the burgeoning digital creative sector. This research seeks to analyze the policy dynamics underpinning the governance of AI-driven digital copyright within Indonesia. It employs a normative juridical methodology, incorporating statutory, conceptual, and comparative lenses drawn from legislative texts, doctrinal principles, and pertinent academic sources. The results demonstrate that Indonesia's prevailing copyright structure fails to expressly encompass AI-generated content. Hence, a flexible regulatory strategy is essential, achieved via the revision of normative provisions that preserve human oversight in creation while delineating a precise protective regime for AI-assisted works, thereby fostering expansion in the domestic creative economy.